National Institutes of Health–Defined Chronic Graft-vs.-Host Disease in Pediatric Hematopoietic Stem Cell Transplantation Patients Correlates With Parameters of Long-Term Immune Reconstitution - Lawitschka, Anita; Gueclue, Ece Dila; Januszko, Angela; Körmöczi, Ulrike; Rottal, Arno; Fritsch, Gerhard; Bauer, Dorothea; Peters, Christina; Greinix, Hildegard T.; Pickl, Winfried F.; Kuzmina, Zoya (Frontiers in Immunology, 2019)
Recent data revealed the importance of immune reconstitution (IR) for the evaluation of possible biomarkers in NIH-defined cGVHD and its clinical aspects. In this large pediatric study (n=146) we have analyzed whether cellular and humoral parameters of IR in the long-term follow-up (FU) with a special emphasis on B-cell reconstitution correlate with NIH-defined cGVHD criteria. HYPOTHESIS: We were especially interested, whether meaningful cGVHD biomarkers could be defined in a large pediatric cohort. We here demonstrate for the first time in a highly homogenous pediatric patient cohort that both cGVHD (n=38) and its activity were associated with the perturbation of the B-cell compartment including low frequencies of CD19+CD27+ memory B-cells and increased frequencies of circulating CD19+CD21low B-cells, a well-known hyperactivated B-cell subset frequently found elevated in chronic infection and autoimmunity. Notably, resolution of cGVHD correlated with expansion of CD19+CD27+ memory B-cells and normalization of CD19+CD21low B-cell frequencies. Moreover, we found that the severity of cGVHD had an impact on parameters of IR and that severe cGVHD was associated with increased CD19+CD21lowB-cell frequencies. When comparing the clinical characteristics of the active and non active cGVHD patients (in detail at time of analyses) we found a correlation between activity and a higher overall severity of cGVHD, which means that in the active cGVHD patient group were more patients with a higher disease burden of cGVHD - despite similar risk profiles for cGVHD. Our data also provide solid evidence that the time point of analysis regarding both HSCT-FU and cGVHD disease activity may be of critical importance for the detailed investigation of pediatric cohorts. Finally, we have proven that the differences in risk factors and patterns of IR, with cGVHD as its main confounding factor, between malignant and non-malignant diseases, are important to be considered in future studies aiming at identification of novel biomarkers for cGVHD.